2018
DOI: 10.1002/ccd.27917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percutaneous paravalvular leak closure on hemolysis

Abstract: Objective To study the effect of percutaneous paravalvular leak closure on hemolysis. Background Although transcatheter PVL closure reduces heart failure and mortality in symptomatic patients with paravalvular leaks (PVL), little is known about its effect on hemolysis. Methods We retrospectively analyzed patients undergoing transcatheter mitral or aortic PVL closure (January 2005–December 2016) at Mayo Clinic. Patients with anemia or abnormal hemolysis markers (LDH, haptoglobin) were included in the analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…The results of Panaich et al, are consistent with the concept of micro‐shear forces etiology for valve‐induced hemolysis. Closure of leaks around mechanical valves rather than biologic valves was much more likely to result in a hematological success, and the more leaks plugged, the better, would fit nicely with reducing or modifying the high‐energy jets and the microenvironment conducive for hemolysis.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The results of Panaich et al, are consistent with the concept of micro‐shear forces etiology for valve‐induced hemolysis. Closure of leaks around mechanical valves rather than biologic valves was much more likely to result in a hematological success, and the more leaks plugged, the better, would fit nicely with reducing or modifying the high‐energy jets and the microenvironment conducive for hemolysis.…”
supporting
confidence: 67%
“…Dr. Panaich, and colleagues from the Mayo Clinic, have reviewed their experience with paravalvular leak closure and its association with subsequent hemolysis. They retrospectively, over a decade of experience, found 168 patients who underwent percutaneous closure and had significant evidence of hemolytic anemia before the procedure.…”
mentioning
confidence: 99%
“…For example, Ruiz et al reported a substantial decrease in the percentage of patients who required blood transfusion or erythropoietin injections after percutaneous PVL repair from 56% to 5% . On the contrary, in another study of 168 patients with PVL, blood transfusion requirements decreased only modestly after percutaneous repair from 34% to 21% . These inconsistencies may be related to the variable definitions of hemolysis and the degree of PVL reduction achieved.…”
Section: Management Of Cardiac Prosthesis‐related Hemolysismentioning
confidence: 99%
“…PVL is a common complication during surgical valve replacement and has been reported in 2% to 10% of aortic valve replacements (AVR) and 7% to 17% of mitral valve replacements (MVR) . Cardiac surgeons have been searching for an effective way to tackle PVLs for a long time.…”
Section: Commentmentioning
confidence: 99%
“…Paravalvular leakage (PVL) is one of the most well‐recognised complications of prosthetic valve replacement. It is quite common and can be seen in 2% to 10% of replacements in the aortic position . However, no unified standard procedure for managing this complication exists.…”
Section: Introductionmentioning
confidence: 99%